Germination of spores and gametophytes of "Polystichum montevidense" (Spreng.) Rosenst. ("Dryopteridaceae") - J. Chambi, Cristina; M. Cardozo, Rubén (Botanica Complutensis, 2013)
A description is made of characteristics of the germination of spores, gametophytic development and adult gametophyte structure of Polystichum montevidense (Spreng.) Rosenst. obtained by sterile culture. It was found that sporangia produce 32 monolete spores with crested perispore. The germination of Vittaria-type spores occurs three days after sowing. Gametophyte development is of the Aspidium type. The laminar gametophytes have only one type of glandular trichomes, with secretion of trichomes has a lipid nature, distributed on the edge of the lamina and a few on the surface. It is reported for the first time that adult gametophyte cells have oil droplets. Sexual expression is manifested in gametophytes of more than 100 days old, with only female gametophytes. All this is illustrated with pictures recorded with light microscopes and a scanning electron microscope.